KEBIJAKAN PENDIDIKAN MBKM DAN EVALUASI IMPLEMENTASI MBKM - Giantomi Muhammad Giantomi (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
The Independent Learning Campus (MBKM) policy made by the government is based on goodwill to respond to very rapid changes in various aspects of life. Learning transformation is needed to be able to equip and prepare higher education graduates to become a superior generation, a generation that is responsive and ready to face the challenges of the times, without being uprooted from the cultural roots of their nation. These challenges must be faced primarily by universities as parties that have a dominant domain in educating and training students. Therefore, a thorough evaluation of the implementation of various MBKM policies is required, so that the achievement of these policy objectives can be realized in an effective and measurable manner. Through a study of various relevant literatures with analytical descriptive techniques, this research was conducted on the basis of the importance of evaluating MBKM policies, starting from the juridical aspect, implementation in the field, to the challenges faced by the policy.